2009
DOI: 10.1128/jvi.00880-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B-Cell Depletion on Viral Replication and Clinical Outcome of Simian Immunodeficiency Virus Infection in a Natural Host

Abstract: Simian immunodeficiency virus (SIV)-infected African nonhuman primates do not progress to AIDS in spite of high and persistent viral loads (VLs). Some authors consider the high viral replication observed in chronic natural SIV infections to be due to lower anti-SIV antibody titers than those in rhesus macaques, suggesting a role of antibodies in controlling viral replication. We therefore investigated the impact of antibody responses on the outcome of acute and chronic SIVagm replication in African green monke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 77 publications
(103 reference statements)
1
49
0
Order By: Relevance
“…Key features of SIV infection in SMs and AGMs include (i) acute infection characterized by a vigorous but transient inflammatory response to the virus, followed by low levels of immune activation throughout the chronic phase of infection (7,28,39); (ii) preservation of healthy levels of circulating and lymph node-based CD4 ϩ T cells in ϳ80 to 90% of animals (30,31,36,40,41,54); (iii) significant early depletion of mucosal CD4 ϩ T cells but relative preservation of the Th17 subset (12,19,39); (iv) stable or recovering levels of mucosal CD4 ϩ T cells and absence of microbial translocation during chronic infection (19,39); and (v) chronic infection characterized by a short in vivo life span of productively infected cells (18,44). The observation that adaptive immune responses to SIV only partially control virus replication in SIV-infected natural hosts (13,14,52,71) indicates that these animals avoid immunodeficiency by mechanisms that are ostensibly different from those described in HIV-infected long-term nonprogressors/elite controllers (LTNP/EC), in whom virus replication is extremely low (35,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key features of SIV infection in SMs and AGMs include (i) acute infection characterized by a vigorous but transient inflammatory response to the virus, followed by low levels of immune activation throughout the chronic phase of infection (7,28,39); (ii) preservation of healthy levels of circulating and lymph node-based CD4 ϩ T cells in ϳ80 to 90% of animals (30,31,36,40,41,54); (iii) significant early depletion of mucosal CD4 ϩ T cells but relative preservation of the Th17 subset (12,19,39); (iv) stable or recovering levels of mucosal CD4 ϩ T cells and absence of microbial translocation during chronic infection (19,39); and (v) chronic infection characterized by a short in vivo life span of productively infected cells (18,44). The observation that adaptive immune responses to SIV only partially control virus replication in SIV-infected natural hosts (13,14,52,71) indicates that these animals avoid immunodeficiency by mechanisms that are ostensibly different from those described in HIV-infected long-term nonprogressors/elite controllers (LTNP/EC), in whom virus replication is extremely low (35,47).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated the mechanisms by which natural hosts of SIVs limit disease progression and have concluded that lack of AIDS is not due to control of viral replication through exquisite immune responses, as viral loads (VLs) in natural hosts are similar to those observed during pathogenic human immunodeficiency virus (HIV)/SIV infections (46) and SIV-specific adaptive immune responses are not quantitatively or qualitatively different from those mounted during pathogenic infection (10,13,14,25,26,68,70). Instead, the lack of disease progression relies on an adaptation of these natural hosts to control the deleterious indirect consequences of SIV infection, i.e., excessive levels of immune activation, T cell proliferation, and apoptosis (11,28,39,53,56).…”
mentioning
confidence: 99%
“…In vivo analyses suggest that Sab92018ivTF faithfully reproduced the properties of its parental strain, which has been extensively characterized (10,14,15,17,(41)(42)(43)(44)(45). All four Sabaeus monkeys infected with the Sab92018ivTF clone maintained high viral loads without developing immunodeficiency during follow-up.…”
Section: Discussionmentioning
confidence: 91%
“…In each case, this was done by intravenous inoculation of plasma, followed by the harvest of plasma from the experimentally infected animal at peak viral replication (10,41). The plasma stocks of Sab92018 have already been studied extensively in vitro and in vivo, and the biological properties of this strain are thus well known (10,14,15,17,(41)(42)(43)(44)(45). To clone Sab92018, we first generated two full-length SIVagmSab proviruses (A5 and E2), using conventional PCR and cloning techniques.…”
mentioning
confidence: 99%
“…The slow progression to AIDS-like symptoms, if at all, in these species share important parallels with HIV-1 infected individuals who are long-term non-progressors and with HIV-2 infected individuals who typically exhibit a less severe clinical course , thereby providing clues about protective immune correlates of HIV infection that will undoubtedly influence vaccine and therapeutic design. It has also become increasingly apparent that immune factors alone may not influence the course of disease, as targeted CD4+ T-cell, CD8+ T-cell or CD20+ B-cell in vivo depletion via cell-specific antibody infusion in sooty mangabeys or AGM had negligible effects on viremia and disease progression [40][41][42], adding an additional layer of complexity and also highlighting that the virus itself needs to be taken into account. Continued research on the intricate interplay between host and virus factors in natural NHP hosts will continue to shed light on mechanisms that may have applications for health preservation in individuals already living with HIV infection.…”
Section: Old World Nhp Natural Hostsmentioning
confidence: 99%